a) (a + 3)(a - 1) +(a - 7)(a +5)
b) (2b - 5)(3 - 2b) - (3b + 2)(b - 6)
c) -7c2(5c - 4) +(3c2 + c)(6 - 2c)
d) 3m(m - 4)(5m + 2) - m(2m + 3)(4-3m)
e) -2x(3x - 5y) - (x + 2y)(3x - y)
Z obliczeniami proszę ​


Odpowiedź :

Odpowiedź:

a) a2-a+3a-3+a2+5a-7a-35=2a2-38

b)6b-2b2-15+10b-3b2-18b+2b-12-5b2-27=-5b2-27

c)-35c3+28c2+18c2-6c3+6c-2c2=-41c3+44c2+6c

d)3m(5m2+2m-20m-8)-m(8m-6m2+12-9m)=15m3+6m2-60m2-24-8m2+6m3-12m+9m2=

=21m3-53m2-36

e) - 6x2+10xy-(3x2-xy+6xy-2y2)=

= -6x2+10xy-3x2+xy-6xy+2y2= - 9x2+5xy+2y2

Licze na naj